Sexual dimorphism of the frequency of significant correlations between the characteristics of body trunk and feet in children aged 4 to 6 years - Mirosław Mrozkowiak (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2021)
Introduction. Relatively few publications have concerned characteristics of body trunk and feet. It is generally suggested that correlations exist between the characteristics of the developing foot and the spinal column. Materials and methods. The examinations conducted in a group of children aged 4 to 6 years allowed for recording 2988 observations, including 1482 girls and 1506 boys, and values of 87 characteristics that described body trunk and feet. The test stand for the measurement of the selected parameters using the photogrammetric method consisted of a personal computer, software, screen and printer, and a projection-reception device with a camera. Conclusion 1. The general number of body trunk characteristics having significant correlations with feet parameters in females was slightly higher. The number of relationships in sagittal and frontal planes was the same in both sexes. The characteristics that differentiated males from females were found mainly in transverse and frontal planes. 2. The number of feet characteristics that most often showed significant correlations with body trunk parameters was higher in girls than in boys. These were mainly characteristics concerning width and length, longitudinal arch and disorders in the position of the feet. The characteristics that differentiated boys described only the longitudinal arch of the feet.